1996
DOI: 10.1080/009841096161843
|View full text |Cite
|
Sign up to set email alerts
|

LOW-LEVEL m-XYLENE INHALATION ALTERS PULMONARY AND HEPATIC CYTOCHROME P-450 ACTIVITY IN THE RAT

Abstract: m-Xylene is a commonly used industrial solvent that has been shown to alter mixed-function oxidase (MFO) activity, in an organ- and isozyme-specific pattern, following intraperitoneal administration of the solvent. The purpose of this work was to determine whether similar alterations occurred in cytochromes P-450 (CYP) following m-xylene inhalation, the primary route of occupational exposure. A single 6-h exposure to m-xylene resulted in the inhibition of aryl hydrocarbon hydroxylase (AHH) activity in the lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Blood levels of o-xylene were in the same range (0.7-2.3 µmol/g) as those observed after similar (300 ppm, 6 h) inhalation exposures to m-or p-xylene Foy et al, 1996).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Blood levels of o-xylene were in the same range (0.7-2.3 µmol/g) as those observed after similar (300 ppm, 6 h) inhalation exposures to m-or p-xylene Foy et al, 1996).…”
Section: Discussionmentioning
confidence: 54%
“…Intraperitoneal (ip) administration or inhalation of xylene and xylene isomers decrease rat pulmonary cytochrome P-450 content and related enzyme activities such as ethoxyresorufin O-dealkylase (EROD; CYP1A1) activity, benzyloxyresorufin O-dealkylase (BROD; CYP2B1) AHH activity, and n-hexane hydroxylation activity (Toftgard & Nielsen, 1982;Elovaara et al, 1987;Pyykko et al, 1987;Foy et al, 1996), while increasing liver microsomal P-450 content and MFO-related enzymatic activities (Elovaara et al, 1980;Savaolainen et al, 1978;Toftgard et al, 1981). Of the three isomers, o-xylene has been the least studied, likely because it is a lesser component of xylene mixtures and is less utilized in industry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated a marked selectively in the effects of endo-and xenobiotics on monooxygenase activities. For instance, inhalation exposure of rats to m-xylene produced selective increases of hepatic methoxyresourfin O-dealkylase and N-nitrosodimethylamine demethylase activities without affecting other monooxygenase activities toward the substrates benzo[a]pyrene, benzyloxyresorufin, 7-ethoxyresorufin, and 2-aminofluorene (Foy et al, 1996). The nature of the possible E2 modulation of xenobiotic metabolism requires further investigation .…”
Section: Discussionmentioning
confidence: 97%
“…Cytochromes P-450 1A1 and 1B1 are involved in metabolic activation of carcinogenic PAH and hydroxylation of mammary carcinogen 17b -estradiol (E2) (Spink et al, 1992;Hayes et al, 1996;. These carcinogen-and estrogen-metabolizing cytochromes P-450 1A1 and 1B1 are expressed in many tissues, including liver, kidney, lung, and mammary glands (Sutter et al, 1994;Foy et al, 1996). Cytochromes P-450 1A1 and 1B1 are responsive to the modulatory effects of xenobiotics.…”
mentioning
confidence: 96%